Pengaruh Konservatisme Akuntansi, Pengukuran Akuntansi, Pengungkapan Modal Sosial, dan Kualitas Informasi Akuntansi Terhadap Tanggung Jawab Sosial Perusahaan - Adellia Pratiwi; Fatchan Achyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Corporate social responsibility is a sustainable decision made by the company to act ethically, contribute to the economic development of the wider community, and improve the quality of employees, as well as achieving a balance between economic justice issues, environmental issues, and meeting the needs of shareholders and stakeholders. This study aims to analyze the effect of accounting conservatism, accounting measurement, disclosure of social capital, and quality of accounting information on corporate social responsibility in non-financial companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. Sampling was carried out using purposive sampling technique. Hypothesis testing is carried out using the classical assumption test, multiple linear regression analysis, model feasibility test (F test), t test, and coefficient of determination analysis. The results of this study prove that the disclosure of social capital affects corporate social responsibility. While accounting conservatism, accounting measurement, and the quality of accounting information have no effect on corporate social responsibility.